1988
DOI: 10.1090/s0002-9939-1988-0964853-5
|View full text |Cite
|
Sign up to set email alerts
|

Alternative version of Shapley’s theorem on closed coverings of a simplex

Abstract: Sperner’s theorem as formulated by Ky Fan is dual to the KnasterKuratowski-Mazurkiewicz theorem. Shapley’s theorem is a generalization of the Knaster-Kuratowski-Mazurkiewicz theorem. This paper points out that Shapley’s theorem is a generalization of Sperner’s theorem as well, by establishing an alternative version of Shapley’s theorem. Applications to the multiperson cooperative game theory are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The following intersection theorem on the unit simplex is due to Ichiishi [6] and can be considered as the dual of the Shapley Lemma.…”
Section: Qedmentioning
confidence: 99%
See 1 more Smart Citation
“…The following intersection theorem on the unit simplex is due to Ichiishi [6] and can be considered as the dual of the Shapley Lemma.…”
Section: Qedmentioning
confidence: 99%
“…The reformulation of this theorem given by Fan [1] and Freidenfelds [2] can also be found in Scarf [14] and is known as Scarf's lemma. Further generalizations of intersection theorems on the unit simplex can be found in Scarf (13], Shapley [15], Gale [5], Freund [4], Ichiishi [6] and Joosten and Talman [S]. bToreover, generalizations of intersection theorems to thf, cube or simplotope are stated in Freund [4], van der Laan, Talman and Van der llcyden [I I], van dcr l,aan and Talman [12] and Talman [17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prove the intersection theorems, a non-constructive proof of the existence of a connected set of constrained equilibria containing both trivial constrained equilibria is given using Browder's fixed point theorem. The intersection theorems of Chapter 7 generalize the well-known results on the unit simplex given in Knaster, Kuratowski, and Mazurkiewicz (1929) (KKM Lemma), in Sperner (1928) and Scarf (1967) (Sperner Lemma), in Shapley (1973) (KKMS Lemma), and in Ichiishi (1988) (Ichiishi Lemma). Moreover, the results can be used to sharpen the usual formulation of the Sperner Lemma on the unit cube.…”
Section: Introductionmentioning
confidence: 52%
“…The KKM Lemma and the Sperner Lemma can be used to prove Brouwer's fixed point theorem and also to show the existence of a Walrasian equilibrium of an economy. Both the KKMS Lemma and the Ichiishi Lemma are very useful when showing the non-emptiness of the core of a cooperative game, see Shapley (1973), Ichiishi (1988), and Shapley and Vohra (1991). The Gale Lemma is used in Gale (1984) to show the existence of a Walrasian equilibrium in an economy with indivisible commodities.…”
Section: Introductionmentioning
confidence: 99%
“…It will be shown that a socially stable game has a non-empty socially stable core. To do so, we formulate an intersection theorem on the unit simplex that generalizes the well-known intersection theorem used by Shapley (1973) (see also Herings, 1997;Ichiishi, 1988;van der Laan et al, 1999). Since socially stable games have a non-empty socially stable core, they also have a non-empty core.…”
Section: Introductionmentioning
confidence: 99%